2016
DOI: 10.1080/01916599.2016.1161535
|View full text |Cite
|
Sign up to set email alerts
|

Race, polygenesis and equality: John Crawfurd and nineteenth-century resistance to evolution

Abstract: The nineteenth-century Orientalist and ethnologist, John Crawfurd, publicly rejected Charles Darwin's theory of evolution in 1868. Crawfurd was a leading advocate of polygenesis but also a supporter of racial equality. In 1820 he published his History of the Indian Archipelago, where he advocated granting household suffrage to all races in the British colonies. After finishing a career in the East India Company in 1828 he became the foremost expert on South-East Asia in Britain. Crawfurd became a regular write… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The unstable unity of these commitments, reflected as much in political, economic, and legal argumentation as in historical and ethnographic analysis, have supplied ample material for scholarly disagreement. Hagiographies of Crawfurd have credited his polygenism with an egalitarian-inclusive appreciation of human plurality, to which they attribute his “liberal” and “democratic” credentials as an imperial reformer (Knapman 2016; Knapman 2017, 74–92; Wong 2018). Skeptics, by contrast, have underscored his explicit somatization of social difference into racial “types” and his brash proclamations of European superiority as evidence of (at best) “soft racism” (Ellingson 2001, 309–20; Krishnan 2007; Quilty 1998; 2018).…”
Section: From Civilization and Savagery To Capitalist Racializationmentioning
confidence: 99%
“…The unstable unity of these commitments, reflected as much in political, economic, and legal argumentation as in historical and ethnographic analysis, have supplied ample material for scholarly disagreement. Hagiographies of Crawfurd have credited his polygenism with an egalitarian-inclusive appreciation of human plurality, to which they attribute his “liberal” and “democratic” credentials as an imperial reformer (Knapman 2016; Knapman 2017, 74–92; Wong 2018). Skeptics, by contrast, have underscored his explicit somatization of social difference into racial “types” and his brash proclamations of European superiority as evidence of (at best) “soft racism” (Ellingson 2001, 309–20; Krishnan 2007; Quilty 1998; 2018).…”
Section: From Civilization and Savagery To Capitalist Racializationmentioning
confidence: 99%
“…The intensification of anti-Black racism Britain was associated with the advent of pseudo-scientific doctrines that caused many British people to doubt the very humanity of Black people. From the 1830s onwards, many British people were attracted to the theory of polygenesis, which rejected the Biblical teaching that all humans were descended from a single couple and instead taught that each of the five races of man had evolved separately from primates (Knapman 2016 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The issue that the different races were separate species and the practice of slavery may be explained in terms of 19th-, 20th-and 21st-century scholarship of polygenesis which started gaining traction in the 1850s (Knapman 2016;Young 1995). This scholarship advocates the notion that as a separate species, Europeans enjoyed individual rights which they did not share with African or Asian peoples.…”
Section: Dynamics Of the Body And Coloniality Of Powermentioning
confidence: 99%
“…Indigenous people's physical appearance, customs and beliefs were used to justify their subjugation as slaves. Many studies have demonstrated the interconnections among polygenesis, imperialism and slavery (Desmond and Moore 2009;Knapman 2016). The monogenesis scholars argue that as one broad family, all humans share a common ancestor and should therefore have the same rights to equality.…”
Section: Dynamics Of the Body And Coloniality Of Powermentioning
confidence: 99%